Cloud ETL Architecture for Streaming Analytics: An End-to-End Framework for Real-Time Data Processing and Intelligence - Sarath Babu Gosipathala, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The exponential growth of data-generating sources including Internet of Things (IoT) devices, mobile applications, and enterprise systems has created unprecedented challenges in data ingestion, processing, and analytics. Traditional batch-oriented Extract-Transform-Load (ETL) architectures struggle to meet the demands of modern real-time analytics, where millisecond-level latency and continuous data availability are critical requirements. Existing approaches often suffer from scalability limitations, inflexible schema management, inadequate integration between batch and stream processing, and insufficient governance mechanisms for ensuring data quality and compliance. This research presents a comprehensive cloud-based ETL architecture specifically designed for streaming analytics that integrates real-time processing layers, multi-zone storage strategies, machine learning pipelines, and robust governance frameworks. The proposed architecture leverages modern cloud-native technologies including Apache Kafka for event streaming, Apache Flink for stream processing, Delta Lake for transactional data management, and cloud data warehouses for analytical workloads. The implementation demonstrates significant improvements in data freshness with sub-second latency for 95% of events, processing throughput exceeding 500,000 events per second, and data quality scores above 98% across all pipeline stages. The architecture achieves 99.9% system availability while maintaining full compliance with GDPR and HIPAA regulations. This framework provides organizations with a scalable, reliable, and maintainable solution for building modern data platforms that seamlessly integrate streaming and batch analytics, enabling data-driven decision-making at unprecedented speeds.
Keywords: Cloud ETL Architecture; Streaming Analytics; Real-Time Data Processing; Apache Kafka; Delta Lake; Machine Learning Pipeline; Data Governance